Single-ion conductivity enhancement for the composite polymer electrolytes based on Li(PVAOB)/PPEGMA for lithium-ion batteries - Soydan, Ali Murat; Bozkurt, Ayhan (Springer Heidelberg, 2018)
In the present work, a series of single-ion conducting composite polymer electrolytes based on lithium polyvinyl alcohol oxalate borate (Li(PVAOB)) and poly(polyethylene glycol methacrylate) (PPEGMA) were produced. PEGMA was polymerized into PPEGMA, and the Li(PVAOB) was prepared from poly (vinyl alcohol) (PVA), oxalic acid, and boric acid. Li(PVAOB) was blended with PPEGMA at different stoichiometric ratios to obtain a single-ion conducting system. All the electrolytes were characterized by Fourier transformation infrared spectroscopy (FT-IR), thermogravimetry analysis (TGA), differential scanning calorimeter (DSC), and scanning electron microscopy (SEM) techniques. These results verified the interaction between host and guest polymers, sufficient thermal stability within the measured conductivity domain, and the homogeneity of the composite electrolytes. The effect of PPEGMA onto the ionic conductivity was investigated using impedance spectroscopy. The Li(PVAOB)-60PPEGMA is the optimum content, and this sample has a maximum ionic conductivity of 3 x 10(-4) S/cm at 100 A degrees C which is approximately five orders of magnitude higher than neat Li(PVAOB). Activation energy (E (a) ) of ionic transport decreased from 11.9 to 0.27 kJ/mol, suggesting a much faster ionic mobility for higher PPEGMA-containing samples.
Keywords: Polyvinyl alcohol; Poly(polyethylene glycol methacrylate); Ionic conductivity; Single-ion conductors; Polymer electrolytes